Effect of stevia substitution on physical, chemical and sensory properties of low-calorie apricot jam - Basmaa Saaduldeen Sheet (Zien Journals, 2022)
A standard sample of apricot jam was prepared and sucrose was replaced with Stevia sweetener (Rebaudioside A), one of the glycoside stevia compounds, with replacement percentages of 25, 50 and 75%. The physical, chemical and sensory properties of all treatments were studied while they were stored for 60 days. It was found from the results that the highest significant value was obtained at the end of the storage period in the values of each indicators of the total acidity percentage of treatment T3 amounted to 0.893% and the percentage of total soluble solids for standard treatment T0, which amounted to 66.270%. while the least significant value was at the end of the storage period in The values of each indicators of pH for treatment T2 which reached 3.190 and T3 which reached to 3.187 and the concentration of vitamin C in treatment T0 amounted to 7.477 mg/100 g and the percentage of moisture in the standard treatment T0 amounted to 28.413% in the same period. The type of treatments and the storage period affected the sensory properties (taste, odor, color and general appearance) of apricot jam, and the degrees of acceptance of all treatments were high at the beginning of storage, but decreased at the end. Replacing the sucrose in them with rebaudioside A by 25 and 50%, respectively, as the use of these two percentages hid the bitter taste left by the sweetener after tasting, and the taste was somewhat similar to the taste of standard treatment T0 at the beginning and end of storage, as well as improving the color, flavor and general appearance in them. T3 was not accepted by the assessors despite the high color and general appearance due to the bitter taste left by the sweetener after tasting with the increase in the proportion of substitution
Keywords: Apricot jam; Sweetener; Stevia; Rebaudioside